The ascent of SOAPbox: A new generation of open access publishing bubbles up in Trinity College Dublin - Brennan, Niamh; Collins, Shane; Doyle, Linda; Shenton, Helen (Septentrio Conference Series, 2019)
Watch the VIDEO. ‘The Open Science revolution will be led by early-career researchers.’ Professor Linda Doyle (Dean of Research, Trinity College Dublin). Major challenges in scholarly communication worldwide have occurred over the past twenty years, but real change has been slow. However, this generation of early career researchers looks likely to finally transform the culture. SOAPbox is a drive led by Trinity College Dublin students to rapidly transform their publishing culture and processes to open access, and in doing so, to fully integrate them into the dynamically-evolving open research environment. While student open access publishing is not new, SOAPbox is distinguished by its agility, its scale and its collective focus and ambition, sustained by its alignment with global and institutional policies and objectives. This has enabled SOAPbox to capture the imagination of a university and, more than any other single initiative, galvanise its community into positive engagement with open access. In this presentation, we outline SOAPbox, its rapid progress and the cultural factors that define it. We explore how this multidisciplinary, inter-generational Open Science community of practice works; we identify early learnings from the project and provide insights into the key issues facing early-career researchers engaged in Open Science publishing. Trinity College Dublin has a history of leadership and collaboration in Open Science, technically (e.g. early CRIS/IR integration; eDeposit Ireland) and from the policy perspective (e.g. EURAB Scholarly Publication Group (Chair, 2007); EC OSPP Board and Working Group representation; Ireland’s National Open Research Forum). In 2018, the Dean of Research and the College Librarian created the TCD Open Scholarship Taskforce which includes faculty deans, researchers, library & HR personal, IT professionals and students. Central to this initiative is an understanding that the successful transition to Open Science requires radical changes in how we approach and value the practice of research. The Taskforce supports projects like SOAPbox that have a transformative effect on research culture. We will explore the SOAPbox Key Signifiers of Transformation: The Big Bang. Very rapid platform development with lightning-fast transformation of a significant number of journals (student-run alongside illustrious academic journals); Inclusiveness. A multi-disciplinary Open Science publishing community of practice across all disciplines and all research career stages (undergraduate and postgraduate students – alongside senior academics managing centuries-old journals); Ethical, Sustainable, Global Responsibility. Supporting positive societal, economic and cultural impact of research, with a specific emphasis on the U.N. Sustainable Development Goals; Cultural Change: an embedded, creative training and education strand, employing innovation expertise, a Certificate in Scholarly Communication (an additional extrinsic motivator) and periodic surveys to inform an understanding of the experience; Alignment: with the strategic goals of the University and with its graduate attributes, championed by the Dean of Research and supported by the Graduate Students’ Union. SOAPbox is a scholar-led, community-driven, inclusive publishing initiative which has embraced the spirit of ‘glocalisation’. It instills a life-time commitment to Open Science amongst its participants, changing the world, from one university out.